Internalization and experience: Japanese banks’ international expansion, 1980–1998 - Qian, Lihong; Delios, Andrew (Journal of International Business Studies, 2008)
We use an interdisciplinary approach to investigate multinational banks’ foreign activities. We bridge core concepts from the stages theory of internationalization to internalization theory, to extend the literature on the defensive expansion hypothesis. Unlike the primarily aggregate levels of analysis employed in previous research on multinational banking, we utilize a firm-level analysis of the internationalization experiences of 21 Japanese banks in the period 1980–1998. We find that banks undertake foreign direct investment to secure internalization benefits by following their existing clients, and to achieve economies of scale in the application of their intangible assets in international markets. The magnitude of these relationships, however, is contingent upon the level of a bank's experience in the host countries. Consistent with predictions from internationalization theory, we find that the motivations for international expansion can change over time.